Company financing in the United Kingdom : a flow of funds model - Bain, A. D.; Day, Colin Leslie; Wearing, A. L. (London : Robertson, 1975)
The book provide an answer to the difficulties in interpreting macroeconomic financial forecasts. It also examines the company investment and stock building to profitability and transactions in financial markets.
Includes index.
Bibliography: p. 137-138.
usc 23/10/18
Loans
Keywords: Corporations; Flow of funds; Great Britain